MicroRNA-195 inhibits the proliferation and invasion of pancreatic cancer cells by targeting the fatty acid synthase/Wnt signaling pathway - Zhichao Xu; Chunli Li; Hui Qu; Huiling Li; Qiaoyan Gu; Jing Xu (Tumor Biology)
Emerging evidence suggests that microRNAs are critical regulators of cancer development and progression. MicroRNA-195 has been reported as a cancer-related microRNA in many human cancers. However, the role of microRNA-195 in pancreatic cancer remains largely unknown. Here, we show that microRNA-195 is downregulated in pancreatic cancer tissues and cell line. Also, we show that overexpression of microRNA-195 inhibits the proliferation and invasion of pancreatic cancer cells, whereas suppression of microRNA-195 promotes proliferation and invasion. We show that microRNA-195 directly targets the fatty acid synthase enzyme and negatively regulates the expression of fatty acid synthase. Also, we show that fatty acid synthase expression is inversely correlated with microRNA-195 expression in pancreatic cancer tissues. Moreover, our results show that microRNA-195 inhibits Wnt signaling in pancreatic cancer cells. By restoring fatty acid synthase expression, we were able to reverse the antitumor effects of microRNA-195 in pancreatic cancer cells. Taken together, our findings show that microRNA-195 inhibits pancreatic cancer cell proliferation and invasion by regulating the fatty acid synthase/Wnt signaling pathway, suggesting a tumor suppressive role for microRNA-195 in the development and progression of pancreatic cancer. Thus, inhibiting fatty acid synthase by microRNA-195 may serve as a novel therapeutic approach for the treatment of pancreatic cancer.